Exploiting supramolecular interactions to produce bevacizumab-loaded nanoparticles for potential mucosal delivery - Ferreira, Leonardo M.B. [UNESP]; Alonso, Jovan D. [UNESP]; Kiill, Charlene P. [UNESP]; Ferreira, Natália N. [UNESP]; Buzzá, Hilde H.; Martins de Godoi, Denis R. [UNESP]; de Britto, Douglas; Assis, Odilio Benedito G.; Seraphim, Thiago V.; Borges, Júlio César; Gremião, Maria Palmira D. [UNESP] (Elsevier, 2018)
Monoclonal antibody (mAb) delivery is gaining importance for local, systemic, and route-specific targeting. The mucus constitutes the main barrier for this type of delivery. In the present study, we aimed to develop a drug delivery platform by integrating mucus penetrating and mucoadhesive agents into a single system. Our hypothesis is that by combining these opposing functions, this system could have its properties modulated according to specific purposes. Self-assembly studies were conducted using three classes of building blocks: the protein drug bevacizumab (BVZ), mucus-penetrating polyanion dextran sulfate (DS), mucoadhesive polycations trimethylchitosan (TMC) and chitosan oligosaccharides (COS). We obtained two types of nanoparticles by manipulating supramolecular interactions between the components. Binary protein-polyanion (BVZ/DS) nanoparticles showed size of approximately 150 nm and a negative zeta potential. Ternary protein-polyanion-polycation (BVZ/DS/COS) nanoparticles were obtained using COS and exhibited 350 nm and a positive zeta potential. Assisted by calorimetric information, we demonstrated that building stable ternary nanoparticles carrying positive charges were not possible using the polycation TMC due to its thermodynamic constraints. Furthermore, spectroscopy analysis and CAM assay indicated that BVZ continued structurally and functionally stable after its incorporation into the nanoparticles. These two types of nanoparticles exhibited different behaviors when interacting with mucin, as shown by DLS and AFM studies. While the negatively charged particles promoted dispersion of the mucin network, suggesting a mucus penetrating effect of DS, the positively charged particles formed aggregates, probably caused by the mucoadhesive effect of COS. These results highlight the importance of understanding the role of supramolecular interactions, responsible for forming drug delivery systems containing complex molecules, such as proteins and polymers.
Keywords: Bevacizumab; Drug delivery platform; Mucoadhesion; Mucus penetration; Polymeric nanoparticles; Supramolecular interactions